Mining the Gap! Fostering Creativity and Innovative Thinking. (2015) - Brand, Gordon; Hendy, Lesley; Harrison, Rachel
Abstract: Current educational strategies limit us to teaching from a sterile model without the nurturing of creativity beyond creative necessity. This we believe is due to the un-enlightened understanding and use of 'creativity' as a tool within teaching practice. We all think we know what creativity is but if we were to challenge the convention and de-construct the process of what we think and understand creativity to be we would realise that creativity is so much more. The boundaries of its definition are and always have been subjective and in being so become blurred. We need to 'pull-focus' on creativity to enhance the value of such a precious commodity. We have the unique opportunity to develop and inspire beyond functional learning and help create a more purposeful, innovative synthesis for both teacher and student. Creativity is a way to expand the learning opportunities through the lens of something that inspires us. With an original approach to fostering creativity our conclusion will address how creativity can direct education to allow fulfilment of the needs of an ever expanding world but more importantly give individuals the stimulation to ignite their imaginations and foster their confidence to actually conceive what they can perceive.